The Impact of Adenotonsillectomy on Mean Platelet Volume in Adenotonsillar Hypertrophy - Arastou, Shima; Shahraki, Alireza; Karimi Galugahi, Mahboobeh; Rabbani Anari, Mahtab; Akbari Dilmaghani, Nader (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2018)
Background: Chronic adenotonsillar hypertrophy which causes airway obstruction and obstructive sleep apnea is the most common indication for adenotonsillectomy in children. Obstructive sleep apnea is almost always associated with adenotonsillar hypertrophy in this age group. Mean platelet volume (MPV) is an indicator of the platelet size. Platelet size reflects the platelet function and activation. Larger platelets have denser granules and higher thrombosis potential. So higher MPV levels are correlated with higher platelet activity and inflammation intensity. Increased platelet activity has a great role in atherosclerosis, ischemic heart disease and cardiovascular morbidity and mortality. Purpose: The aim of this study is to evaluate the MPV level in patients who underwent adenotonsillectomy. Methods: In this longitudinal study, 37 patients with chronic adentonsillar hypertrophy who underwent adenotonsillectomy were enrolled. MPV levels before and 3 weeks after surgery were recorded and compared with paired comparison analysis. The significance level was less than 0.05. Results: MPV levels were 8.7 ±0.9 and 8.2±1.2 fL, before and after adenotonsillectomy, respectively. A statistically significant decrease was noted in MPV levels following surgery (P=0.022). Conclusion: MPV levels of the patients with adenotonsillar hypertrophy significantly decreased postoperatively. These results demonstrate that MPV level changes can be reversed and treated by adenotonsillectomy.